Effectiveness of Health Education Toward Personal Hygiene During Menstruation Among Adolescent Girls - Aminah, Aan; Mayunita, Abela (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2024)
Aims: knowing the effectiveness of providing health education about personal hygiene to adolescent girls who are menstruating. Method: quasi-experimental with one group pretest-posttest design. The sample in this study were some 10th grade students of SMAN I Jatisari in July 2023 as many as 75 people. The sampling technique was random sampling. Results: The knowledge of adolescent girls about personal hygiene before being given health is mostly poor knowledge (78.7%) and after being given health education is mostly good knowledge (56%). Health education can effectively improve the knowledge of adolescent girls about personal hygiene (p value 0.000). Conclusions: Health education can effectively improve the knowledge of adolescent girls about personal hygiene. It is hoped that health workers will be more active in conducting counseling on personal hygiene during menstruation so that young women get knowledge related to this and apply good and correct personal hygiene behaviour.